Understanding why fat, oil and grease (FOG) bioremediation can be unsuccessful - Gurd, Caroline; Villa, Raffaella; Jefferson, Bruce (Elsevier, 2020)
Commercial kitchen wastewaters are typically strong organic and fat-rich effluents, often identified as major contributors to fatberg formation and associated blockages in sewers. Experimental trials were done using synthetic kitchen wastewater to understand the complex reactions involved in microbial remediation in grease traps/separators prior discharge in sewers. The principle organic components (FOG, carbohydrate and protein nitrogen), were varied using ranges observed in a previous study on real kitchen wastewater characterisation. A model bacterium, Bacillus licheniformis NCIMB 9375, was used to evaluate microbial utilisation of the different organic fractions in relation to fat, oil and grease (FOG) degradation. Novel results in the treatment of these effluents showed that, the presence and concentration of alternative carbon sources and the ratio of carbon to nitrogen (COD:N) had great influence on FOG-degradation response. For example, FOG removal decreased from 24 to 10 mg/l/h when glucose was substitute for starch at equivalent concentrations (500 mg/l); and from 26 to 5 mg/l/h when initial COD:N increased from 45:1 to 147:1. The dominant influence of COD:N was validated using a commercial bioadditive and real kitchen wastewater adjusted to different COD:N ratios, confirming the strong influence of kitchen wastewater composition on bioremediation outcomes. These results can therefore have major implications for biological management of FOG in kitchens and sewers as they provide a scientific explanation for bioremediation success or failure.
Keywords: Bioadditives; Bioadditions; Kitchen wastewater; Fatberg; Lipids; FOG